Mindful parenting—A thematic exploration of narratives from Indian mothers - Mazumdar, Ketoki; Parekh, Sneha; Sen, Isha (Frontiers in Global Women's Health, 2023)
Introduction With the global crisis of COVID-19 continuing, Indian mothers have not received adequate attention with respect to their challenges and mothering experiences. The current study explored mindful parenting practices in a cohort of Indian mothers of children aged 10 years and below that emerged in response to the challenges posed by COVID-19. Methods In-depth virtual interviews were conducted with 31 urban Indian mothers to explore their lived experiences of mothering during the global crisis and their engagements with mindful parenting practices. The data were thematically analyzed. Results and Discussion The study identified two overarching themes and nine subthemes. The first theme, pandemic-induced stress, included the sub-themes of increased workload, poor support system, lack of time for self, and emotional and physical distress. The second theme of mindful parenting included the sub-themes of awareness as a mother and around the child, acceptance toward self and the child, empathic understanding of self and the child, active engagement with the child, and emotional regulation. Increased workload on all fronts coupled with poor support and a lack of time for self-contributed to exacerbated emotional and physical stress in mothers. They addressed these concerns posed by their lived experiences by engaging in mindful parenting processes in their mothering practices. Mindfulness-based cognitive therapy, mindfulness-based stress reduction, and mindfulness-based parenting techniques could be explored as possible interventions for mothers to alleviate their distress while drawing attention to larger structural changes and policy-level interventions addressing social issues such as gender inequality and childcare concerns.